Farmers’ perceptions on irrigation water contamination, health risks and risk management measures in prominent wastewater-irrigated vegetable farming sites of Addis Ababa, Ethiopia - Woldetsadik, D.; Drechsel, Pay; Keraita, Bernard N.; Itanna, F.; Gebrekidan, H. (Springer, 2018)
The use of wastewater to produce food crops particularly vegetables is very prevalent in Addis Ababa, Ethiopia. This practice may pose health risks to farm workers and consumers. Hence, the study was designed to evaluate farmers’ perceptions on irrigation water quality, health risks and health risk mitigation measures in four wastewater-irrigated urban vegetable farming sites in Addis Ababa. Data were collected on farm through 263 individual interviews and 12 focus group discussions. The findings showed that despite differences in levels of knowledge and awareness on health risks, farmers appear informed about the contamination of their irrigation water. The difference in perception to quality consideration of Akaki River/irrigation water is highlighted by the result of Kruskal–Wallis H test analysis which shows significant mean value (1.33) of positive perception toward the water quality by male than female farmers. Interestingly, significant difference (p < 0.05) in mean values of awareness toward problems of eating unwashed vegetables is also found between male and female farmers where females seemed to be more aware. Conversely, no significant difference was found in mean value of perception and awareness toward vegetables quality. Among the perceived health risks, skin problems were top-rated health risk while eye burn, sore feet and abdominal pains were rated low across the four farming sites. Although statistically not significant, perception toward consumption-related health risk differed with gender: females assigned relatively high mean score. Irrespective of the farming site and gender differences, the most accepted health risk reduction measures were health promotion programs and cessation of irrigation before harvesting. In view of crop restriction measures, females assigned significantly (p = 0.044) low mean score to planting non-food produce. Akaki-Addis farmers suitability perceptions of planting non-food produce and non-raw eaten crops were significantly (p < 0.001) higher than the other farming sites. Therefore, effective site and gender-specific educational programs have the potential for clarifying farmers and consumers’ risks and risk management perceptions and improving practical knowledge, which in turn may help identify adoption barriers, opportunities and incentives.